Self-Care Technologies and Collaboration - Nunes, Francisco; Fitzpatrick, Geraldine (International journal of human-computer interaction, 2015)
The self-management of a chronic condition is a collaborative activity, performed by patients and carers. However, to date, self-care technologies have been mostly designed for individual use. This article uses a case study of people living with Parkinson's disease to (a) illustrate how patients and carers collaborate in self-management, (b) discuss the reasons why self-care technology is designed for individual use, and (c) explore the implications of recognizing collaborations for the design of self-care technologies. This work is based on a qualitative study with interviews and observations with people living with Parkinson's. The analysis illustrates how people living with Parkinson's collaborate in self-care to build a good life. In particular, it exemplifies how the complex interplay of actions and of patients and carers enables the different self-care activities to take place. To further integrate self-care technology in everyday life, designers need to consider collaborations when studying the context, conceptualizing a technology, and planning an evaluation.